2018
DOI: 10.13057/biodiv/d190207
|View full text |Cite
|
Sign up to set email alerts
|

Autecology and morphological properties of sandalwood (Santalum album) in Pidie District, Aceh, Indonesia

Abstract: Nurochman D, Matangaran JR, Santosa G, Suharjito D, Sari RK. 2018. Autecology and morphological properties of sandalwood (Santalum album) in Pidie District, Aceh, Indonesia. Biodiversitas 19: 406-412. IUCN Red List (1998) reported that Santalum album L. as an endangered species. Studies on autecology, association, and the utilization of sandalwood on its natural habitat becomes important to perform conservation of the species. This research was conducted in Teungku Dilaweung Village, Pidie District, Province o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Our assumption is supported by the geographical location of Aceh, which is located adjacent to the Malacca Strait, which was the center of sandalwood trade from NTT to China and India in the 17th century (Blusse and Veen, 2007;Fuller et al, 2011 in the characteristics of sandalwood habitats in Aceh and NTT, including dry land dominated by grasses and shrubs with an average temperature of 24°C to 32°C. The two sites also contain low levels of organic C, N Total, and P, along with a neutral acidity level (Nurochman et al, 2018). Furthermore, Loveless (1992) and Alpert et al (1993) found that despite similar population characteristics, due to the wide geographical or spatial distance between populations, it can cause variations in genetic distance within the population.…”
Section: Datamentioning
confidence: 94%
See 2 more Smart Citations
“…Our assumption is supported by the geographical location of Aceh, which is located adjacent to the Malacca Strait, which was the center of sandalwood trade from NTT to China and India in the 17th century (Blusse and Veen, 2007;Fuller et al, 2011 in the characteristics of sandalwood habitats in Aceh and NTT, including dry land dominated by grasses and shrubs with an average temperature of 24°C to 32°C. The two sites also contain low levels of organic C, N Total, and P, along with a neutral acidity level (Nurochman et al, 2018). Furthermore, Loveless (1992) and Alpert et al (1993) found that despite similar population characteristics, due to the wide geographical or spatial distance between populations, it can cause variations in genetic distance within the population.…”
Section: Datamentioning
confidence: 94%
“…Current information on sandalwood utilization in other areas in Indonesia are limited, especially in the western region, including Aceh. Sandalwood is known by the local community in Aceh as "Ceundana" or "Bak Cin," and the trees have been used by utilizing the logs for wardrobe or air freshener without any further processes (Nurochman et al, 2018). Aceh Statistical Agency reported that total production of sandalwood logs in Aceh was 357,124 tons from 2003 to 2015.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results on vegetation analysis of the four habitats of G. versteegii in western part of Flores Island (Tables 1-4) suggest that this species can grow in a broad range of habitats with varying vegetation compositions and floristic structures. It means that these species do not require specific association with particular vegetation, for example as in the case of Indian sandalwood (Santalum album) (Nurochman et al 2018). This is an important finding for population enhancement efforts as it implies that G. versteegii can be planted in varying vegetation conditions, whether it is cultivated in monoculture plantation system, planted along with other species in polyculture system, such as agroforestry, or even reintroduced into its natural habitat with high species richness.…”
Section: Gyrinops Versteegiimentioning
confidence: 99%
“…are documented in Africa [ 21 , 22 ], similar information is lacking for Osyris lanceolata [ 23 ]. There are peculiar ecological and genetic aspects of O. lanceolata which need to be understood and aligned with strategies for responsible management, in particular hemiparasitism, complex distribution patterns and low survival rate [ 24 , 25 ]. These broad attributes raise the following questions which require critical analysis: (i) What is the distribution, taxonomy and ethnobotany of O. lanceolata ?…”
Section: Introductionmentioning
confidence: 99%